Synthesis and applications of graphene and graphene-based nanocomposites: Conventional to artificial intelligence approaches - Tariq, Waheed; Ali, Faizan; Arslan, Chaudhry; Nasir, Abdul; Gillani, Syed Hamza; Rehman, Abdul (Frontiers in Environmental Chemistry, 2022)
Recent advances in graphene research has enabled the utilization of its nanocomposites for numerous energies based and environmental applications. Advancement in graphene-based polymer nanocomposites is observed in present day world with an emphasis on synthesis and application. Graphene-based nanocomposites shows astonishing electrical, mechanical, chemical and thermal characteristics. Different methods including covalent and non-covalent methods, chemical based deposition approach, hydrothermal growth, electrophoresis deposition and physical deposition are used for synthesis of graphene nanocomposites (GNC’s). Chemical methods are most viable route for producing graphene in small quantities at low temperatures. The technique can also produce graphene films on a variety of substrate materials. Use of Artificial Intelligence (AI) for synthesis of AI-created nano-particles is extensively explored in recent past. These nanocomposites materials have excellent applications in environmental, energy, and agricultural sectors. Due to high carrier mobility graphene and related materials enhances the photocatalytic performance of semiconductor materials. Similarly, these materials have high potential in pollutant removal especially heavy metals due to high surface area. This article highlights synthesis of graphene-based nanocomposites and their applications in different sectors.